Biotechnology Innovation: Increasing Plant Genetic Diversity for Ecosystem Balance and Food Security - Hendarto, Totok; Arshad, Imran (CV. Bimbingan Belajar Assyfa, 2024)
This article discusses innovations in biotechnology through genetic transformation and somaclonal engineering with the aim of increasing plant genetic diversity, which is very important for ecosystem balance and food security. Unlike previous studies that focused more on structural genetic variation, this article highlights the application of modern technologies such as the use of Agrobacterium tumefaciens and tissue culture techniques. These methods aim to create plants with superior properties, strengthen their ability to adapt to extreme environmental conditions, and support biodiversity conservation efforts. The analysis shows that the combination of molecular technology and somaclonal engineering can produce plant varieties that are more durable, productive, and adaptive to climate change. This innovation is expected to contribute significantly to supporting global food security and biodiversity conservation, by providing sustainable solutions to current environmental challenges. The integration of this technology not only enriches plant genetic variation but also contributes to the stability of the wider ecosystem. With this progress, it is hoped that food production can increase and be more stable even when faced with uncertain climate change.